2013
DOI: 10.3390/land2020158
|View full text |Cite
|
Sign up to set email alerts
|

Interdependences between Smallholder Farming and Environmental Management in Rural Malawi: A Case of Agriculture-Induced Environmental Degradation in Malingunde Extension Planning Area (EPA)

Abstract: The objective of this article was to develop a deeper understanding of the interdependences between smallholder farming and the state of environmental management in rural Malawi. We examined the agricultural local governance framework in Malingunde Extension Planning Area (EPA), its contribution to food security and how it conflicts with overall land and forest resources management. The charcoal production process was discussed in line with its implications for agricultural production and environmental sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Intervention in the landscape such as proper forest, agricultural, soil and water management and initiatives in alternative livelihoods, energy and good governance have double benefits in building adaptive capacity of smallholder farmers and resilience of the agro-ecology. This is in parallel to the study by Munthali and Murayama [44] that indicated the interdependences between smallholder farming and environmental management. Farmers responded that institutional integration, collective action and improvement of the declining resources conditions in the landscapes could help to bring higher odds of outcomes in climate-specific and climate-relevant capacities, and enable to build the resilience and adaptive capacity of farmers.…”
Section: Discussionsupporting
confidence: 77%
“…Intervention in the landscape such as proper forest, agricultural, soil and water management and initiatives in alternative livelihoods, energy and good governance have double benefits in building adaptive capacity of smallholder farmers and resilience of the agro-ecology. This is in parallel to the study by Munthali and Murayama [44] that indicated the interdependences between smallholder farming and environmental management. Farmers responded that institutional integration, collective action and improvement of the declining resources conditions in the landscapes could help to bring higher odds of outcomes in climate-specific and climate-relevant capacities, and enable to build the resilience and adaptive capacity of farmers.…”
Section: Discussionsupporting
confidence: 77%
“…The smallholder sector is further subdivided into subsistence and commercial smallholder farming (Chirwa and Matita, 2012). The smallholder sector employs 80% of the rural population (Munthali and Murayama, 2013). The population of rural smallholder farmers in Mzimba North is 113,852 (Mzimba North District Agriculture Office, 2014).…”
Section: Background Informationmentioning
confidence: 99%
“…Firewood and charcoal are the major sources of household energy supply for 99% of our survey respondents. Interestingly, due to affordability issues, most of the population connected to the national electricity grid across the country use it mainly for lighting, while still using charcoal as well for cooking and heating (Munthali & Murayama 2013). Lack of affordable alternative energy sources remains an important root cause of deforestation, threatening the sustainability of the resource base.…”
Section: Integrated Catchment Management and Protection Of The Resourmentioning
confidence: 99%